Short-Term High-Salt Diet Increases Corin Level to Regulate the Salt–Water Balance in Humans and Rodents. (9th September 2017) - Zhang, Jiao; Yin, Yanjun; Chen, Lili; Chu, Chao; Wang, Yang; Lv, Yongbo; He, Ming; Martin, Marcy; Huang, Po-Hsun; Mu, Jian-Jun; Shyy, John Y-J; Yuan, Zu-Yi
Abstract: BACKGROUND: Dietary sodium and potassium affect the fluctuation in blood pressure (BP) and renal function. Corin, with its enzymatic activity to convert pro-atrial natriuretic peptide (pro-ANP) to biologically active ANP, regulates BP, cardiac, and renal functions. We investigated whether corin expression responds to a high-salt (HS) diet to regulate salt and water balance. METHODS: Forty-two volunteers followed 3 sequential diets for 7 days each: a low-salt (LS) diet (3.0 g/day NaCl), a HS diet (18.0 g/day NaCl), followed by an HS diet with K + supplementation (HS + K + ) (18.0 g/day NaCl and 4.5 g/day KCl). RESULTS: Corin level was higher with the HS diet than the LS and HS + K + diets and was positively correlated with systolic BP (SBP) and 24-hour urinary Na + and microalbumin (U-mALB) excretion. In rodents, serum and renal levels of corin were transiently increased with the HS diet and were decreased if the HS diet was continued for up to 7 days. HS loading increased SBP, 24-hour urinary Na +, U-mALB excretion, and the expression of proprotein convertase subtilisin/kexin-6 (PCSK6), a corin activator. Knockdown of PCSK6 or corin in high salt-treated M1-cortical collecting duct (M1-CCD) cells increased the expression of aquaporin 2 (AQP2) and β-epithelial Na + channel (β-ENaC). CONCLUSIONS: Short-term HS may induce the PCSK6–corin–ANP–AQP2/β-ENaC pathway in the kidney. Enhanced serum corin level in humans and rodents is positively correlated with HS-induced SBP and 24-hour urinary Na + and U-mALB excretion, which suggests that corin is involved in the salt-water balance in response to HS intake. CLINICAL TRIALS REGISTRATION: Public Trials Registry Number NCT02915315